The capability of Glossostigma elatinoides to accumulate Al, Mn, Fe and Mg from contaminated landfill leachate through in vitro landscape ecological model system - Othman, Rashidi; Mat Ali, Qurratu Aini; Hj. Baharuddin, Zainul Mukrim; Sahidin, Norhanizan (2015)
The growth of solid waste generation in Malaysia from year 2005 to 2013 statistically has risen from 19,000 tonne to 33,000 tonne per day. This rapid increase mainly affected the number of landfill which is the final disposal destination of solid waste. Landfill is very crucial site which need to be managed properly or it can be hazardous to the living things and also a silent killer. Thus, the landfill treatment to prevent water and soil pollution is widely renowned. Phytoremediation is one of the environmental friendly and economically approaches which using plants to treat soil contamination. Aquatic plants are known to have capability in sequestering heavy metals in phytoremediation. This is because it contains variety in species, high multiplication rate, global distribution and faster in growth. Therefore, this research aimed to assess heavy metals sequestration rate of Glossostigma elatinoides at three different concentrations ranging from low, medium and high (0.5 mol, 1.0 mol and 2.0 mol) of four types of heavy metal (Al, Mn, Fe, Mg) at four different periods of time (week 1 until week 4) through in vitro landscape ecological model system. The results established that there were significant differences between the sequestration rates of the plant, type of heavy metals, level of concentration, period of time and their interactions. This aquatic plant species has capability and resistance over 4 types of heavy metal toxicity. Hence, the high correlation between metal removal in soil and this aquatic plant species indicates that this species can be used effectively for the removal of heavy metals from polluted or contaminated landfill soil of different concentrations.